Geotourism potential of show caves in Poland - Zieliński, Artur; Marek, Aneta; Zwoliński, Zbigniew (Quaestiones Geographicae, 2022)
In the modern world, tourism is a very dynamically growing industry with significant impact on the eco-nomic prosperity of many regions or even countries. The paper presents the geotourism potential of the 12 show (com-mercial) caves in Poland before and during the current pandemic time. Survey results demonstrate that caves are major geotourist attractions. In 2019, they were visited by a total of almost 950,000 people. The attendance might have exceed-ed even a million if the popular Mroźna Cave in the Tatras had not been temporarily closed to visitors due to a rockfall in winter period 2018/2019. In 2020, all the show caves combined were visited by a more than 390,000 people, which amounted to about 41% of the total attendance recorded for 2019. The most visited cave proved to be Smocza Jama (Dragon’s Den) in the centre of Kraków, which recorded almost 422,000 visitors in 2019. A preliminary assessment of the attractiveness of the caves as geosites is given. The most attractive caves as geosites were identified as: Bear Cave, Upper Wierzchowska Cave, and Bat Cave. It is possible to confidently assert that the celebration of the International Year of Caves and Karst (IYCK) in 2021–2022 will increase interest in caves and translate into a revival of cave tourism.